2004
DOI: 10.1038/ni1119
|View full text |Cite
|
Sign up to set email alerts
|

Early B cell factor cooperates with Runx1 and mediates epigenetic changes associated with mb-1 transcription

Abstract: Cd79a (called mb-1 here) encodes the Ig-alpha signaling component of the B cell receptor. The early B cell-specific mb-1 promoter was hypermethylated at CpG dinucleotides in hematopoietic stem cells but became progressively unmethylated as B cell development proceeded. The transcription factor Pax5 activated endogenous mb-1 transcription in a plasmacytoma cell line, but could not when the promoter was methylated. In this context, early B cell factor (EBF), a transcription factor required for B lymphopoiesis, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
167
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 43 publications
11
167
1
1
Order By: Relevance
“…Previously, we concluded that EBF increases the accessibility of mb-1 promoter DNA (22). In turn, this facilitates DNA binding and activation of the promoter by Pax5.…”
Section: -Oht-dependent Ebf and Pax5mentioning
confidence: 79%
See 2 more Smart Citations
“…Previously, we concluded that EBF increases the accessibility of mb-1 promoter DNA (22). In turn, this facilitates DNA binding and activation of the promoter by Pax5.…”
Section: -Oht-dependent Ebf and Pax5mentioning
confidence: 79%
“…Unlike M.10 cells, M.2 cells are refractory to activation by Pax5 because their mb-1 promoters are uniformly hypermethylated in relatively inaccessible chromatin (21,22). Following incubation with 4-OHT (Fig.…”
Section: -Oht-dependent Ebf and Pax5mentioning
confidence: 99%
See 1 more Smart Citation
“…3). Alternatively, CLPs can differentiate to T-cells through Notch1 activation, which is negatively regulated by PAX5 [166][167][168] . Recent studies have shown the role of FOXP1 in the transition of pro-B cells to pre-B cells, a step which is also controlled by IRF4/MUM1 and IRF8 169,170 .…”
Section: Do Lymphoid Malignancies Arise From Mutations That Deregulatmentioning
confidence: 99%
“…In particular, the binding of EBF1 to chromatin has been shown to correlate with dimethylation of Lys4 of histone H3 (Treiber et al 2010b). In addition, the function of EBF1 has been associated with SWI/SNF-dependent remodeling of chromatin and DNA demethylation of some promoters (Maier et al 2004;Gao et al 2009;Boller et al 2016). However, no physical interaction between EBF1 and SWI/SNF proteins has yet been demonstrated.…”
mentioning
confidence: 99%